58 indícios sobre o corpo (Revista da Universidade Federal de Minas Gerais, 2012)
A body’s material. A body isn’t empty. It’s full of other bodies. It’s also full of itself. A body’s immaterial. It’s a drawing, a contour, an idea. The body is also a prison for the soul. The body’s a prison, or a god. Why indices? Because there’s no totality to the body, no synthetic unity. There are pieces, zones, fragments. Why 58 indices? Because 5 + 8 = the members of the body, arms, legs and head, and the the eight regions of the body: the back, the belly, the skull, the face, the buttocks, the genitals, the anus, the throat.